Uji Aktivitas Antiinflamasi Ekstrak Etanol Daun Sereh Wangi (Cymbopogon nardus L.) Dengan Metode Denaturasi Protein - Eni Kartika Sari; Beta Ria Erika Marita Dellima; Fatimah Nur Azizah (Lumbung Farmasi: Jurnal Ilmu Kefarmasian, 2025)
Long-term use of steroid and non-steroidal antiinflammatory drugs (NSAIDs) will cause side effects such as liver damage, digestive disorders and other side effects. Therefore, alternative treatments are needed that utilize the potential of natural ingredients. Lemongrass leaves have active compounds of flavonoids, tannins, steroids, saponins and alkaloids which have the potential to act as antiinflammatory. This study aims to determine the antiinflammatory activity of ethanol extract of citronella leaves using the protein denaturation method. Bovine serum albumin (BSA) as protein for testing. The test was carried out in vitro based on its effect on the inhibition of protein breakdown using BSA as a test medium which was damaged by heating.The results showed that the ethanol extract of citronella leaves has antiinflammatory activity with its ability to inhibit protein breakdown, where the higher the concentration, the higher the % inhibition of inhibition of BSA protein damage. A % inhibition value of more than 20% can be said to have antiinflammatory activity. The IC50 value of the ethanol extract of citronella leaves is 19,608 ppm and diclofenac sodium is 29,124 ppm. The IC50 value of the ethanol extract of citronella leaves and diclofenac sodium is in the very active category because the IC50 value is less than 50 ppm. This indicates that the antiinflammatory activity of the ethanol extract of citronella leaves is higher than diclofenac sodium so that it has the potential to be used as an antiinflammatory agent.